The Role of the Headteacher in Promoting Religious Moderation in Primary Schools - Lalu Andrean Hidana; Zahrotun Ni’mah Afif; Solechan Solechan; Jirayut Decharoen (At Tadbir: Islamic Education Management Journal, 2026)
This study aims to analyse the strategic role of headteachers’ leadership in promoting religious moderation at primary school level, as well as to explore strategies for internalising this concept and the factors influencing them. This study employs a qualitative approach using a case study design. Data was collected through in-depth interviews with headteachers and teachers, participatory observation of school activities, and documentation. Data analysis was carried out through the stages of data condensation, data presentation, and drawing conclusions based on Miles, Huberman’s and Saldana interactive model. The research findings indicate that headteachers fulfil a multidimensional role as vision articulators, cultural architects and instructional leaders. The internalisation of the value of moderation is carried out systematically through pedagogical integration in learning, the fostering of inclusive interactions, and the strengthening of symbolic capital through leading by example. The key enabling factors were found to be the collective commitment of the school community and a supportive organisational climate. However, this process faces external challenges in the form of family backgrounds and external environmental influences that are sometimes at odds with the school’s values. This study underscores the importance of synergy between structural and cultural approaches in educational leadership to ensure the sustainability of efforts to promote religious moderation in primary schools.